2015
DOI: 10.1111/tpj.12793
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive identification of mutations induced by heavy‐ion beam irradiation in Arabidopsis thaliana

Abstract: SUMMARYHeavy-ion beams are widely used for mutation breeding and molecular biology. Although the mutagenic effects of heavy-ion beam irradiation have been characterized by sequence analysis of some restricted chromosomal regions or loci, there have been no evaluations at the whole-genome level or of the detailed genomic rearrangements in the mutant genomes. In this study, using array comparative genomic hybridization (array-CGH) and resequencing, we comprehensively characterized the mutations in Arabidopsis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 62 publications
5
98
0
Order By: Relevance
“…radiation and bring about a large deletion and/or rearrangement of a DNA segment (Shikazono et al, 2005;Tanaka et al, 2010;Hirano et al, 2012). A genome-wide analysis of structural changes induced by ion-beam irradiation in Arabidopsis revealed that deletions as large as 1.2 Mbp could occur (Hirano et al, 2015). Such a large deletion can involve the loss of multiple linked genes and, therefore, may explain some of the coincidental changes observed in this study.…”
Section: Changes In Seed Isoflavonesmentioning
confidence: 92%
“…radiation and bring about a large deletion and/or rearrangement of a DNA segment (Shikazono et al, 2005;Tanaka et al, 2010;Hirano et al, 2012). A genome-wide analysis of structural changes induced by ion-beam irradiation in Arabidopsis revealed that deletions as large as 1.2 Mbp could occur (Hirano et al, 2015). Such a large deletion can involve the loss of multiple linked genes and, therefore, may explain some of the coincidental changes observed in this study.…”
Section: Changes In Seed Isoflavonesmentioning
confidence: 92%
“…The size of deletions increases with increasing value of the linear energy transfers (LETs) of heavy-ion beams (Kazama et al, 2011(Kazama et al, , 2013Hirano et al, 2012). Whole-genome identification using HTS confirmed that base substitutions, deletions, insertions and chromosomal rearrangements were induced at the whole-genome level (Hirano et al, 2015). Thus, it is now possible to determine any type of mutation using HTS.…”
mentioning
confidence: 97%
“…In A. thaliana, fast-neutron-induced mutations were revealed to be mainly base substitutions and small deletions (Belfield et al, 2012). We have previously identified the mutation spectrum of the heavy-ion beam in A. thaliana as comprising base substitutions, deletions, insertions and chromosomal rearrangements (Hirano et al, 2015). The size of deletions increases with increasing value of the linear energy transfers (LETs) of heavy-ion beams (Kazama et al, 2011(Kazama et al, , 2013Hirano et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations